The effects of tapering of three different percentages on physiological variables among futsal players - Saleh, M. Y.; Abdullah, A. M.; Taha, A. A. (International Journal of Disabilities Sports and Health Sciences, 2024)
The purpose: this study aimed to determine the effect of a two-week tapering period on physiological variables by reducing three different percentages of volume (30%, 50%, 70%) while maintaining high training intensity on young futsal players. Method: An experimental design was used. The research sample was chosen from players of the talent school in Nineveh Governorate for the year 2023-2024, totaling 18 players (6 players per group). A paired student's t-test was used to process the interaction effect between pre- and post-training, and an ANCOVA test was used to determine the differences between the three groups. Results: Tapering with a 50% reduction rate led to the development of all physiological variables of performance in the Bruce test (p<0.005), aerobic (p<0.025) and anaerobic work (p<0.018), VO2max (p<0.028), and blood Lactate (p<0.031). while tapering with a 30% reduction rate led to the development of aerobic work (p<0.33) and VO2max (p<0.044). Tapering with a 70% reduction rate led to the development of achievement in the Bruce test(p<0.01), anaerobic work (p<0.046), and LA (p<0.030). While there were no significant differences among the three groups in physiological variables of performance in the Bruce test (p<0.151), aerobic (p<0.085) and anaerobic work (p<0.343), VO2max (p<0.181), and LA (p<0.166). Conclusions: the tapering by 50%, showed a more balanced development in aerobic and anaerobic work, VO2max, and LA compared to to the tapering by 30% reduction, which developed only aerobic work and VO2max, and to the tapering 70% reduction, which developed anaerobic work and LA.